Variables yet and future help in the development of human resources - معتوق, محمد (Journal of Economics and Administrative Sciences, 2016)
This research aims to study a range of yet and future variables that can affect human resources in Iraq and public organizations that influence the size of each, and the extent of its contribution to the development of human resources through the National Investment Commission of Baghdad. The identified research problem in a set of questions was the most important, what are the variables that help in the development of human resources to the Investment Commission of Baghdad theme of the search, in order to achieve the goal of research and answer questions about the problem, applied research on both the research community's (55) individual executives and employees. Researcher has identified a range of these variables is the (technological advances and information, technical training, changes in the patterns of administrative organizations, and intellectual capital, and social). Wan Shan hiring of these variables in the work of public organizations in Iraq that leads to increase the prospects of the development of the Iraqi economy and increase domestic and foreign investment. The questionnaire used a key tool for the collection of data and information as well as personal interviews and cohabitation field, and the study of historical documents and reports of human resources working in the organization surveyed.For the purpose of analyzing data and information, the researcher used a number of statistical methods including: the percentage, the arithmetic mean is likely, and the standard deviation and factor analysis, research has come to a number of conclusions were highlighted: The process of rehabilitation technical and invest in public organizations Iraqi (bodies domestic investment) of the most important factors of the development of human resources which, as it increases the role of technology in the life of organizations, day after day. One of the most important recommendations are (involvement of employees in developmental courses in universities and academic institutions to enhance their experience and increase the efficiency and skills of human resources in those organizations.